2008
DOI: 10.1121/1.2888489
|View full text |Cite
|
Sign up to set email alerts
|

Cortical sensitivity to periodicity of speech sounds

Abstract: Previous non-invasive brain research has reported auditory cortical sensitivity to periodicity as reflected by larger and more anterior responses to periodic than to aperiodic vowels. The current study investigated whether there is a lower fundamental frequency (F0) limit for this effect. Auditory evoked fields (AEFs) elicited by natural-sounding 400 ms periodic and aperiodic vowel stimuli were measured with magnetoencephalography. Vowel F0 ranged from normal male speech (113 Hz) to exceptionally low values (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
(25 reference statements)
7
24
1
Order By: Relevance
“…In MEG, the pitch specific response comprises a subcomponent of the N 1 m after pitch onset (Gutschalk et al, 2004;Krumbholz et al, 2003) and of the sustained response that continues for the duration of the periodic sound (Gutschalk et al, 2002) (also referred to as the "pitch onset response", POR, and the "sustained pitch response", SPR). A similar dependence of sustained activity on stimulus periodicity is observed for vowels, for which the degree of periodicity jitter determines the perceived vowel "roughness" (Yrttiaho et al, 2009;Yrttiaho et al, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…In MEG, the pitch specific response comprises a subcomponent of the N 1 m after pitch onset (Gutschalk et al, 2004;Krumbholz et al, 2003) and of the sustained response that continues for the duration of the periodic sound (Gutschalk et al, 2002) (also referred to as the "pitch onset response", POR, and the "sustained pitch response", SPR). A similar dependence of sustained activity on stimulus periodicity is observed for vowels, for which the degree of periodicity jitter determines the perceived vowel "roughness" (Yrttiaho et al, 2009;Yrttiaho et al, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…vowel probes. The larger amplitude coupled with a more anterior source location in the periodic than in the aperiodic condition was similar to that found in several studies indicating cortical sensitivity to sound periodicity (Hertrich et al, 2000;Alku et al, 2001;Tiitinen et al, 2005;Lütkenhöner et al, 2006;Soeta and Nakagawa, 2008;Yrttiaho et al, 2008Yrttiaho et al, , 2009Yrttiaho et al, , 2010. This result might be taken to suggest that the population activated by the periodic stimulus is larger than that activated by the aperiodic stimulus and, thus, includes a distinct periodicity-sensitive subpopulation.…”
Section: Discussionsupporting
confidence: 86%
“…The periodicity-specific adaptation and the periodicityspecific displacement in the N1m source location were, however, observed for both the 800 ms-and the 200-ms ISI. Several studies addressing the encoding of sound periodicity have found evidence for a specialized cortical population or populations responsive to sound periodicity (Griffiths et al, 1998(Griffiths et al, , 2001Hertrich et al, 2000;Alku et al, 2001;Patterson et al, 2002;Gutschalk et al, 2004;Penagos et al, 2004;Tiitinen et al, 2005;Soeta et al, 2005;Soeta and Nakagawa, 2008;Lütkenhöner et al, 2006;Hall et al, 2006;Hall and Plack, 2009;Yrttiaho et al, 2008Yrttiaho et al, , 2009Yrttiaho et al, , 2010Lewis et al, 2009;Schönwiesner and Zatorre, 2008;Griffiths et al, 2010). However, the few data sets that pertain to whether aperiodicity is also encoded by the activation of a specialized population do not seem to converge on the issue.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations